Induction of Fetal Hemoglobin by Introducing Natural Hereditary Persistence of Fetal Hemoglobin Mutations in the γ-Globin Gene Promoters for Genome Editing Therapies for β-Thalassemia - Lu, Dian; Xu, Zhiliang; Peng, Zhiyong; Yang, Yinghong; Song, Bing; Xiong, Zeyu; Ma, Zhirui; Guan, Hongmei; Chen, Bangzhu; Nakamura, Yukio; Zeng, Juan; Liu, Nengqing; et al. (Frontiers in Genetics, 2022)
Reactivation of γ-globin expression is a promising therapeutic approach for β-hemoglobinopathies. Here, we propose a novel Cas9/AAV6-mediated genome editing strategy for the treatment of β-thalassemia: Natural HPFH mutations -113A>G, -114C>T, -117G>A, -175T>C, -195C>G, and -198T>C were introduced by homologous recombination following disruption of BCL11A binding sites in HBG1/HBG2 promoters. Precise on-target editing and significantly increased γ-globin expression during erythroid differentiation were observed in both HUDEP-2 cells and primary HSPCs from β-thalassemia major patients. Moreover, edited HSPCs maintained the capacity for long-term hematopoietic reconstitution in B-NDG hTHPO mice. This study provides evidence of the effectiveness of introducing naturally occurring HPFH mutations as a genetic therapy for β-thalassemia.